Research on the Sustainability of Rural Sanitation Marketing in Vietnam - World Bank (Washington, DC, 2012)
In the 1990s, the Socialist Republic of Vietnam formulated a new policy, strategy, and program to meet the Millennium Development Goals (MDGs) and national targets to improve rural water supply and sanitation. While progress in water supply increased rapidly, progress in sanitation lagged behind. By 1998, just 24 percent of rural Vietnamese households had sanitary toilets, placing the achievement of MDG targets for sanitation by 2015 at risk. The study provides valuable insights to practitioners working on projects related to sanitation marketing.